Is Virtual Reality Training More Effective Than Traditional Physical Training on Balance and Functional Mobility in Healthy Older Adults? A Systematic Review and Meta-Analysis - Liu, Meng; Zhou, Kaixiang; Chen, Yan; Zhou, Limingfei; Bao, Dapeng; Zhou, Junhong (Frontiers in Human Neuroscience, 2022)
Objective The studies showed the benefits of virtual reality training (VRT) for functional mobility and balance in older adults. However, a large variance in the study design and results is presented. We, thus, completed a systematic review and meta-analysis to quantitatively examine the effects of VRT on functional mobility and balance in healthy older adults. Methods We systematically reviewed the publications in five databases. Studies that examine the effects of VRT on the measures of functional mobility and balance in healthy older adults were screened and included if eligible. Subgroup analyses were completed to explore the effects of different metrics of the intervention design (e.g., session time) on those outcomes related to functional mobility and balance. Results Fifteen studies of 704 participants were included. The quality of these studies was good. Compared to traditional physical therapy (TPT), VRT induced greater improvement in TUG (MD = −0.31 s, 95% CI = −0.57 to −0.05, p = 0.02, I2 = 6.34%) and one-leg stance with open eyes (OLS-O) (MD = 7.28 s, 95% CI = 4.36 to 10.20, p = 0.00, I2 = 36.22%). Subgroup analyses revealed that immersive VRT with more than 800 min of total intervention time over 8 weeks and at least 120 min per week and/or designed by the two motor-learning principles was optimal for functional mobility and balance. Conclusion Virtual reality training can significantly improve functional mobility and balance in healthy older adults compared to TPT, and the findings provided critical knowledge of the optimized design of VRT that can inform future studies with more rigorous designs. Systematic Review Registration [https://www.crd.york.ac.uk/PROSPERO/], identifier [CRD42021297085].